2007
DOI: 10.1007/s11126-007-9048-9
|View full text |Cite
|
Sign up to set email alerts
|

State Prison Mental Heath Services Recipients Perception of Care Survey

Abstract: Random samples were requested, but likely only a convenience sample was obtained. However, the positive results suggest the need to strive to enhance patient quality of care ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Way et al . (2007) examined the relationship of prisoners' perception of mental health services and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Way et al . (2007) examined the relationship of prisoners' perception of mental health services and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…The prison mental health population in many ways could be considered analogous to our sample population. There are little data on consumer satisfaction of psychiatric services in prison; however, one New York study demonstrated that 79% of responders agreed that they were satisfied (Way et al 2007). A general prison health services satisfaction survey carried out in Norway demonstrated high levels of dissatisfaction, with those who identified as having poorer physical and mental health being less satisfied with their care (Bjorngaard et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that more communication and better relationships with staff results in greater consumer satisfaction (Duggins & Shaw, 2006), and that a consumer-provider treatment alliance is crucial for successful outcomes (Berk, Berk, & Castle, 2004). Results of a collaborative consumer-provider relationship could include better psychotropic medication compliance (Kilbourne et al, 2006), less cost-related skipping of medication regimens (Wilson, Rogers, Chang, & Safran, 2005), and higher clinician ratings of quality of life outcomes (Way, Sawyer, Kahkejian, Moffitt, & Lilly, 2007).…”
Section: Importance Of Continuity Of Care and Case Management Coordinmentioning
confidence: 99%